2015
DOI: 10.1001/jamaoncol.2015.2607
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Standard for Ductal Carcinoma In Situ Treatment

Abstract: The original goal of mammographic screening was to identify invasive cancers at the earliest stage, because of the superior prognosis of stage I cancers. Prior to the advent of screening, ductal carcinoma in situ (DCIS) made up approximately 3% of breast cancers detected. As we pushed to find smaller and smaller cancers, and targeted calcifications instead of just masses, we began to identify DCIS more frequently. Now DCIS accounts for approximately 20% to 25% of screen-detected breast cancers. The cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 11 publications
3
68
0
Order By: Relevance
“…We soon realized that many of the news articles referred not to our study, but to an accompanying editorial 14 in which Dr. Laura Esserman suggested that our findings support the notion (hers) that women with dcis might not need surgery at all and that the right approach might be to "actively monitor these women, only treating if the cancer progresses" 13 . But all the women in our study underwent surgery for dcis, and based on our findings, we cannot recommend active surveillance or withholding of treatment.…”
Section: Media Responsementioning
confidence: 78%
“…We soon realized that many of the news articles referred not to our study, but to an accompanying editorial 14 in which Dr. Laura Esserman suggested that our findings support the notion (hers) that women with dcis might not need surgery at all and that the right approach might be to "actively monitor these women, only treating if the cancer progresses" 13 . But all the women in our study underwent surgery for dcis, and based on our findings, we cannot recommend active surveillance or withholding of treatment.…”
Section: Media Responsementioning
confidence: 78%
“…Rethinking the standard for DCIS treatment is the current research trend (15). There are many papers that distinguish prognosis or analysis of DCIS, an early cancer without invasion, from invasive ductal carcinoma (IDC) (3,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…There are many papers that distinguish prognosis or analysis of DCIS, an early cancer without invasion, from invasive ductal carcinoma (IDC) (3,15,16). In this study, we also analyzed the cases that were upgraded to DCIS and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of incremental cancer detection rate (around 2/1000 examinations) and absolute decrease of recall rate (about 1-1.5%) have been observed after implementation of 3D digital breast tomosynthesis in population-based screening trials (30)(31)(32)(33). Many logistical issues and the role of potential over-diagnosis of DCIS need further evaluation to determine the potential implications and cost of supplemental HHUS, SAUS, combined 2D + supplemental 3D mammographic screening (30)(31)(32)(33)(34)(35)(36). At present, the available data strongly support investment in new large-scale population screening trials that should use a randomized and prospective design.…”
Section: Evidence Based Medicine and Coverage For Supplemental Screeningmentioning
confidence: 99%